Examination of youth sexual and reproductive health transitions in Nigeria and Kenya using longitudinal data - Ilene S. Speizer; David Guilkey; Lisa M. Calhoun; Meghan Corroon; Rick O'Hara (BMC, 2017)
Abstract Background The adolescent (ages 15-19) and young adult (ages 20-24) years are a crucial time as many sexual and reproductive health (SRH) transitions take place in these years. The study of youth SRH transitions in sub-Saharan Africa is limited due to a paucity of longitudinal data needed to examine the timing and circumstances of these transitions. Methods This paper uses recently collected longitudinal data from select urban areas in Kenya and Nigeria that include a large youth sample at baseline (2010/2011) and endline (2014). We control for unobserved heterogeneity in our modelling approach to correct for selectivity issues that are often ignored in similar types of analyses. Results We demonstrate that the transition patterns (i.e., sexual initiation, first marriage, and first pregnancy/birth) differ within and across the urban areas and countries studied. Urban Kenyan youth have more premarital sex and pregnancy than youth from the Nigerian cities. Further analyses demonstrate that more educated and wealthier youth transition later than their less educated and poorer counterparts. Conclusions The findings from this study can be used to inform programs seeking to serve young people based on their varying reproductive health needs in different contexts over the adolescent and young adult years.